2021
DOI: 10.1891/11-t-696
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hemorrhage in the Neonate

Abstract: Pulmonary hemorrhage (PH) is a pathology associated with significant morbidity and mortality, particularly among preterm infants in the NICU. The diagnosis is made when hemorrhagic secretions are aspirated from the trachea concurrent with respiratory decompensation that necessitates intubation or escalated support. The implementation of mechanical ventilation and widespread exogenous surfactant administration have significantly reduced respiratory morbidities. However, when PH develops, death remains the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In contrast, another study showed that no differences in moderate to severe BPD between pulmonary hemorrhage group and non-pulmonary hemorrhage group ( Previous study has de nitely shown that severe RDS and hemodynamically signi cant PDA (hsPDA) are triggers of pulmonary hemorrhage [22]. And the mechanism of pulmonary hemorrhage is mainly related to pulmonary congestion, pulmonary edema and pulmonary small vessel embolism [23]. Moreover, newborns with severe RDS and hsPDA often need longer invasive ventilation, which may increase the possibility of BPD.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, another study showed that no differences in moderate to severe BPD between pulmonary hemorrhage group and non-pulmonary hemorrhage group ( Previous study has de nitely shown that severe RDS and hemodynamically signi cant PDA (hsPDA) are triggers of pulmonary hemorrhage [22]. And the mechanism of pulmonary hemorrhage is mainly related to pulmonary congestion, pulmonary edema and pulmonary small vessel embolism [23]. Moreover, newborns with severe RDS and hsPDA often need longer invasive ventilation, which may increase the possibility of BPD.…”
Section: Discussionmentioning
confidence: 97%
“…According to our present study and long-term clinical experience, a large pleural effusion in PH requires pleural puncture under ultrasound monitoring to drain the effusion, which can reduce patient's dyspnea and facilitate their recovery. Otherwise, the high mortality from PH is almost inevitable (3)(4)(5)(6). Among all the neonatal lung diseases, PH is the most difficult one to be diagnosed by ultrasound.…”
Section: Figurementioning
confidence: 99%
“…It was reported that the prevalence of neonatal PH was 6.7 for 1,000 live births, the rates observed were 8% among newborns <1,500 g, and 11% among newborns <1,000 g ( 3 ). Once PH occurs, the fatality rate can be increased as high as 56.25% ( 4 ), while the survivors also had a higher incidence of bronchopulmonary dysplasia (BPD), cerebral palsy and cognitive delay increased 2.5 times in premature infants with PH, and the incidence of severe periventricular leukomalacia also increased significantly ( 5 , 6 ). Early diagnosis and early treatment are the key to improve the prognosis of PH infants.…”
Section: Introductionmentioning
confidence: 99%
“…Newborn clinical data included gestational age (week), birth weight (g), the severity of BPD, early-onset PH, 1-min Apgar score (A1), 5-min Apgar score (A5), meconium aspiration syndrome (MAS), amniotic fluid contamination, exclusive breastfeeding, neonatal respiratory distress syndrome (NRDS) more than II grades, ventilator-associated pneumonia [ 11 ], septicemia [ 12 ], necrotizing enterocolitis (NEC) requiring surgery, pulmonary hemorrhage [ 13 ], hemodynamically significant PDA [ 14 ], retinopathy of prematurity (ROP) more than II grades, small for gestational age (SGA), sex, age at initiated feeding (day), and time to achieve full enteral feeding (day).…”
Section: Introductionmentioning
confidence: 99%